Orientasi Kewirausahaan dan Orientasi Pasar sebagai Faktor Penentu Kinerja Usaha: Peran Mediasi Keunggulan Kompetitif pada Usaha Mikro dan Kecil Kuliner Halal di Kota Malang - Abdullah As Shoib; Naswan Suharsono; Madziatul Churiyah (Universitas Muhammadiyah Pontianak, 2026)
This study examines the influence of entrepreneurial orientation and market orientation on business performance through the mediating role of competitive advantage among halal culinary MSEs in Malang City. Using a quantitative approach, data were collected from 266 respondents selected via proportional purposive sampling and analyzed using PLS-SEM. The findings reveal that both orientations exert a positive and significant influence on competitive advantage and business performance, with market orientation emerging as the most dominant driver. Competitive advantage partially mediates both relationships. Halal product certification oriented toward consumer needs serves as a critical determinant of market competitiveness.